2013
DOI: 10.1021/jp400914y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Alkyl Chain Length on the Rotational Dynamics of Nonpolar and Dipolar Solutes in a Series of N-Alkyl-N-Methylmorpholinium Ionic Liquids

Abstract: Rotational dynamics of two dipolar solutes, 4-aminophthalimide (AP) and 6-propionyl-2-dimethylaminonaphthalene (PRODAN), and a nonpolar solute, anthracene, have been studied in N-alkyl-N-methylmorpholinium (alkyl = ethyl, butyl, hexyl, and octyl) bis(trifluoromethansulfonyl)imide (Tf2N) ionic liquids as a function of temperature and excitation wavelength to probe the microheterogeneous nature of these ionic liquids, which are recently reported to be more structured than the imidazolium ionic liquids (Khara and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 74 publications
6
94
0
Order By: Relevance
“…Similar effects of alkyl chain have also been observed in studies with RTILs. 40,82 The anion dependence of ν em obtained by using DMASBT (τ life ∼ 0.5 ns) and C153 (τ life ∼ 4 ns) is shown in Table I where representative results for (CH 3 CONH 2 + LiX) DEs at 303 K are presented along with the radii 35,83 of the ions considered. Note the extent of anion dependence of ν em is larger for low lifetime probe.…”
Section: A Interaction In (Rconh 2 + Lix) Des: Alkyl Chain Length Anmentioning
confidence: 99%
“…Similar effects of alkyl chain have also been observed in studies with RTILs. 40,82 The anion dependence of ν em obtained by using DMASBT (τ life ∼ 0.5 ns) and C153 (τ life ∼ 4 ns) is shown in Table I where representative results for (CH 3 CONH 2 + LiX) DEs at 303 K are presented along with the radii 35,83 of the ions considered. Note the extent of anion dependence of ν em is larger for low lifetime probe.…”
Section: A Interaction In (Rconh 2 + Lix) Des: Alkyl Chain Length Anmentioning
confidence: 99%
“…12,13 Possibilities for using neat ILs to control intermolecular interactions have been suggested primarily for cyanine dye self-assemblies. 14 Studies on viscosity of ILs using fluorescent dyes has been a subject of interest, [15][16][17] and the use of fluorescent probes for understanding the structure of ILs, in general, has been recently reviewed. 18 In addition, it was shown that the viscosity of molecular organic media could control the conformation of a conjugated porphyrin dimer (PD), resulting in an array of conformations with two distinct extremes: a planar and a twisted conformation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Many specific features have been observed due to heterogeneous nature of RTILs including the significant difference between their bulk viscosity and micro viscosity, the spatial solvation, and rotational dynamics and other interesting photo physical process of the solute in RTILs . Samanta et al have also shown how the existence of the domain structure of ILs through fluorescence correlation spectroscopy . Role of cation symmetry and tuning the microheterogeneity through size effect of the constituent ions is currently a fascinating area of experimental and computational investigation in IL field …”
Section: Introductionmentioning
confidence: 99%